The Influence Mechanism of Abnormal Immunophilin FKBP52 on the Expression Levels of PR-A and PR-B in Endometriosis Based on Endometrial Stromal Cell Model in Vitro. (3rd April 2021) - Liu, Liling; Cheng, Junping; Wei, Fu; Pang, Lihong; Zhi, Zhifu; Yang, Wenmei; Tan, Weihong
ABSTRACT: As a chaperone protein of progesterone receptor (PR), FK-506 Binding Protein 52 (FKBP52) can enhance the activity of PR, but the mechanism of FKBP52 affecting PR expression levels is difficult to clarify. Here, we report a novel in vitro model of ectopic endometrial stromal cells (ESCM) established through the primary culture method of endometrial stromal cells, which is used to study the details of relationship between FKBP52 abnormality and PR expression level in endometriosis (Ems). At the same time, the clinical study of the relationship between FKBP52 and PR expression levels in endometriosis patients was used to verify our conclusions. The results showed that the expression levels of PR-A mRNA and protein in endometriosis are positively correlated with FKBP52 and the abnormality of FKBP52 leads to the decrease of PR-B mRNA and protein expression. When FKBP52 was deleted or reduced, the expression levels of m RNA and protein of PR-A and PR-B have decreased leading to the proliferation of ectopic endometrium cells (ESC) and the occurrence of endometriosis, which is consistent with the expression levels of clinical endometriosis patients and fully confirms our conclusions and reliability of the model, and has great guiding significance for the research of Ems disease occurrence mechanism and clinical treatment. Graphical abstract: uf0001